GB20 Pharmacopuncture As a Potential Method for Brain Drug Delivery via the Perivascular Spaces - Oxana Semyachkina-Glushkovskaya; Inna Blokhina; Nikita Navolokin; Arina Evsukova; Georgy Karandin; Alexander Khorovodov; Andrey Terskov; Ivan Fedosov; Alexander Dubrovsky; Maria Tzoy; Vasily Ageev; Ilana Agranovich; et al. (Medical Association of Pharmacopuncture Institute, 2022)
Background : The development of new methods of drug brain delivery is a crucial step for the effective therapy of the brain diseases. Pharma- and acupuncture are the forms of alternative therapy of the brain pathology, including an increase in the permeability of blood-brain barrier. However, the mechanisms of pharma- and acupuncture-mediated effects on the brain physiology remain not fully understood. Results : This pilot study on healthy mice clearly demonstrates the Evans Blue spreading in the mouse head and in the brain via the perivascular spaces (PVSs) of the trigeminal structure and the cribriform plate after the dye injection into the Feng Chi point (Galbladder 20, GB20). Conclusion : These results suggest that pharmacopuncture at GB20 can be a perspective method for brain drug delivery via PVSs.